Cultural synergy: Integrating Lamin Dayak Kenyah in English language learning – A need analysis study - Fitriani, Yustina; Gunawan, Muhammad Henry (Univeritas Papua, 2024)
This research aims to identify students' preferences and interests in learning English through Lamin Dayak Kenyah architectural buildings. This research is a mixed research that combines quantitative and qualitative data. The participants were 271 students and 33 English lecturers at universities. The methods used to collect data were classroom observations, surveys, and interviews to identify specific needs faced by students and lecturers when incorporating traditional houses into learning materials. The four fundamental English language skills—listening, reading, writing, speaking—are included in the results. In listening skills, students and lecturers prefer to learn and teach English by watching videos and listening to dialogues or conversations. In reading ability, students and lecturers want to learn with intensive reading, active reading, and critical reading. Regarding writing skills, students and lecturers prefer assignments such as writing descriptive texts and opinion articles. In speaking skills, students and lecturers want to learn through discussion and describing pictures orally. In choosing topics, students and lecturers are interested in the history of local architectural buildings, traditional house design, and the symbolism, color, and meaning of the carvings. Project-based learning (PBL) is the preferred learning method, and learning resources are drawn from videos and interactive learning tools. Future research can utilize these findings to design more targeted instructional materials, leveraging the results of the needs analysis that has been conducted in this study.